Scientific Explanation of the Photoelectric Effect Using Common Objects - Prayogi, S.; Silviana, F.; Zainuddin, Z. (Department of Physics, Faculty of Mathematics and Natural Sciences, 2023)
In this study, a tool that can explain laboratory-scale photoelectric effect events was designed. So that having a tool that can explain the photoelectric effect will make it easier for users to study the nature of light as a particle. This tool is designed according to its function which will know that the photoelectric effect event is not affected by light intensity but is influenced by the frequency of a light source and the wavelength that shines on a metal so that electrons will move from a negative source towards a positive voltage source. A gadget for this experiment was built uses phototubes and cheap LEDs as light sources instead of traditional mercury lamps. Multiple LEDs operating in the wavelength range 470–631 nm can be used to measure the Planck constant to an accuracy better than 10%. By varying the intensity of the LEDs, it is possible to monitor the energy of the electrons and photocurrent with respect to the amount of light. The results show that the voltage applied to the photodiode leg (cathode) has a different value for each color spectrum and the output voltage obtained for each different wavelength, the less light intensity received by the photodiode, the smaller the output voltage value.